The Development of Professional Educators from a Qur’anic Perspective - Fauzi Ananda; Achyar Zein; Zulheddi Zulheddi (JTP - Jurnal Teknologi Pendidikan, 2026)
the Qur’an by revealing the related terms, as well as analyzing the duties of these educators and examining them in relation to teacher competencies. The results of this study are expected to add new perspectives in implementing the duties of educators found in the Qur’an. This type of research is classified as library research, using a qualitative method based on descriptive documents and tending to use analysis with an educational approach, namely collecting Qur’anic verses concerning the duties of educators. The approach used in this study is the science of tafsīr. Meanwhile, the data collection technique uses documentation techniques from primary data sources in the form of Qur’anic verses, supplemented by secondary data sources in the form of books of tafsīr and other supporting books related to the object of the research. The collected research data are then analyzed using the content analysis method through several steps, including: verses concerning the duties of educators, verse analysis, and drawing conclusions on the meanings of the verses. The role and position of professional educators as Ulul Albab. The role and position of professional educators as Ulul Absar. The role and position of professional educators as Ulul Ilmi. The role and position of professional educators as Ulun Nuha. The role and position of professional educators as Ulama. The role and position of professional educators as Ahlu Dhikr. The role and position of professional educators as Al-Rasikhun fil `Ilmi. The role and position of professional educators as Mubashshir.